Caesarean delivery on maternal request: the perspective of the postpartum women - Célia J. L. Sitoe Muhandule; Cristine M. S. Benetti; Laura B. Fogulin; Silvana F. Bento; Eliana Amaral (BMC, 2024)
Abstract Background Caesarean delivery on maternal request (CDMR) is an increasing delivery option among women. As such, we aimed to understand the reasons that led pregnant women to request a caesarean delivery. Methods A phenomenological study was conducted with semi-structured interviews, in a convenience sample, for women who had undergone a CDMR between March and June 2023, in a public reference university hospital in Campinas, Brazil. The interviews were recorded, transcribed and subjected to thematic analysis, supported by Nvivo®, and Reshape®. Results We interviewed eighteen women between 21 and 43 years of age. The reasons for C-section as their choice were: 1) fear of labour pain, 2) fear for safety due to maternal or fetal risks, 3) traumatic previous birth experiences of the patient, family or friends 4) sense of control, and 5) lack of knowledge about the risks and benefits of C-section. Conclusions The perception of C-section as the painless and safest way to give birth, the movement of giving voice and respecting the autonomy of pregnant women, as well as the national regulation, contribute to the increased rates of surgical abdominal delivery under request. Cultural change concerning childbirth and better counseling could support a more adequate informed decision-making about delivery mode.